Fine Mapping to Identify the Functional Genetic Locus for Red Coloration in Pyropia yezoensis Thallus - Yu, Xinzi; Wang, Lu; Xu, Kuipeng; Kong, Fanna; Wang, Dongmei; Tang, Xianghai; Sun, Bin; Mao, Yunxiang (Frontiers in Plant Science, 2020)
Pyropia yezoensis, commonly known as “Nori” or “Laver” is the economically important marine crop. In natural or selected populations of P. yezoensis, coloration mutants are frequently observed. Various coloration mutants are excellent materials for genetic research and in studying photosynthesis. However, the candidate gene controlling the Pyropia coloration phenotype remains unclear to date. QTL-seq, in combination with kompetitive allele-specific PCR (KASP) and RNA-seq, can be generally applied to population genomics studies to rapidly identify genes that are responsible for phenotypes showing extremely opposite traits. Through cross experiments between the wild line RZ and red-mutant HT, offsprings with 1–4 sectors chimeric blade were generated. Statistical analysis revealed that the red thallus coloration phenotype is conferred by a single nuclear allele. Two-pair populations, consisting of 24 and 56 wild-type/red-type single-genotype sectors from F1 progeny, were used in QTL-seq to detect a genomic region in P. yezoensis harboring the red coloration locus. Based on a high-quality genome, we first identified the candidate region within a 3.30-Mb region at the end of chromosome 1. Linkage map-based QTL analysis was used to confirm the candidate region identified by QTL-seq. Then, four KASP markers developed in this region were used to narrow down the candidate region to a 1.42-Mb region. Finally, we conducted RNA-seq to focus on 13 differentially expressed genes and further predicted rcl-1, which contains one non-synonymous SNP [A/C] in the coding region that could be regulating red thallus coloration in P. yezoensis. Our results provide novel insights into the underlying mechanism controlling blade coloration, which is a desirable trait in algae.